2019
DOI: 10.1152/ajpcell.00294.2019
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of transcription factor EB to adipoRon-induced inhibition of arterial smooth muscle cell proliferation and migration

Abstract: Abnormal vascular smooth muscle cell (SMC) dedifferentiation with increased proliferation and migration during pathological vascular remodeling is associated with vascular disorders, such as atherosclerosis and in-stent restenosis. AdipoRon, a selective agonist of adiponectin receptor, has been shown to protect against vascular remodeling by preventing SMC dedifferentiation. However, the molecular mechanisms that mediate adipoRon-induced SMC differentiation are not well understood. The present study aimed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Exercise upregulates the AdipoR1 levels in AD mice brain. AdipoR agonists have been reported to promote TFEB’s nuclear translocation and the expression of TFEB-controlled autophagic genes, such as cathepsin D, lysosomal-associated membrane protein 1 (LAMP1), and ATPase H+ transporting V1 subunit H (Atp6v1h), thereby enhancing lysosomal function and autophagic flux [ 33 , 34 , 35 ]. It is suggested that aerobic exercise may promote the nuclear translocation of TFEB in the brain cells of APP/PS1 mice by upregulating the AdipoR1 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise upregulates the AdipoR1 levels in AD mice brain. AdipoR agonists have been reported to promote TFEB’s nuclear translocation and the expression of TFEB-controlled autophagic genes, such as cathepsin D, lysosomal-associated membrane protein 1 (LAMP1), and ATPase H+ transporting V1 subunit H (Atp6v1h), thereby enhancing lysosomal function and autophagic flux [ 33 , 34 , 35 ]. It is suggested that aerobic exercise may promote the nuclear translocation of TFEB in the brain cells of APP/PS1 mice by upregulating the AdipoR1 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that decreased lysosomal acidification accompanied by impaired autophagic substrate clearance is an important factor in the induction of AD-related pathologies such as Aβ deposition [ 40 ]. TFEB regulates the expression of lysosomal-function-related genes such as LAMP1 and cathepsin D and autophagy-related genes, thereby enhancing the autophagy–lysosomal pathway, reducing neural apoptosis, and exerting neuroprotective effects [ 35 , 49 ]. Drug treatment enhances the autophagolysosomal pathway by activating TFEB, thereby promoting the degradation of toxic proteins in AD models, and PP2A plays an important role in promoting TFEB’s nuclear translocation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study provides evidence for the molecular basis of CYGB contribution to vascular remodeling. VSMC migration is critical in many physiological and pathological processes [23,24]. Herein, we show that overexpression of CYGB provided faster migration rates in the scratch monolayer cell wound assay compared to the control.…”
Section: Discussionmentioning
confidence: 68%
“…Wang et al revealed the contribution of TF EB to adipoRon-induced inhibition of arterial smooth muscle cell proliferation and migration [ 28 ]. In our study, JASPAR software online was used to predict TFs regulating promoters of miR-552 and the ATF4 were determined by qRT-PCR assay.…”
Section: Discussionmentioning
confidence: 99%